Study on beamformer performance with variation in array configuration, number of microphones and array aperture size for the detection of faraway speech signals in outdoor environments - Ko, Bryden Wenyin (2017)
Beamforming has been used since World war II where phased arrays were created for the use of radar systems to detect enemies. Up till today, beamforming has not been obsolete. Instead, it has been upgraded and used for complex systems such as the medical equipment where an image of a baby can be shown through ultrasound.